5(f-9)=-50

Simple and best practice solution for 5(f-9)=-50 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(f-9)=-50 equation:


Simplifying
5(f + -9) = -50

Reorder the terms:
5(-9 + f) = -50
(-9 * 5 + f * 5) = -50
(-45 + 5f) = -50

Solving
-45 + 5f = -50

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '45' to each side of the equation.
-45 + 45 + 5f = -50 + 45

Combine like terms: -45 + 45 = 0
0 + 5f = -50 + 45
5f = -50 + 45

Combine like terms: -50 + 45 = -5
5f = -5

Divide each side by '5'.
f = -1

Simplifying
f = -1

See similar equations:

| -10(s+5)=25 | | 12x^2-59xy+72y^2=0 | | -4(2t+7)=-52 | | 3(f-10)=-21 | | -10(s+2)=43 | | 3x^3=4x+11 | | 2(4s+10)=116 | | 5(2l+7)=135 | | 3(a-10)=3 | | 4cosx+2sinx=3 | | (q-6)*3=9 | | (q-6)*4=9 | | 6(3s+8)=156 | | 5(a-3)=65 | | 8x^2-2xy*-3y^2=0 | | 3+91x=39x+11 | | 2x^2=3x+12 | | 3a^2+a-10=0 | | 24-6x=12-8x | | (A-3)(3a-1)= | | -3.6r-4.5r=-6.48 | | 5.5+2.2n-4.789n=-3.3026 | | -3.5x+3.3x=0.86 | | 2(3x-4)+3(2x+2)=142 | | (x+5)(y-3)=0 | | 4x+11=-43-5x | | -4.3r-2.2r=13 | | (2z+6)(z-2)= | | m+2.6+0.26=3.76 | | xy+5y-3x=15 | | 4.79n+3.9n=-13.035 | | X-0.80X=5159 |

Equations solver categories